Enhancing risk/safety management of HAN-based liquid propellant as a green space propulsion fuel: A study of its hazardous characteristics - Kang, Limin; Liu, Jingping; Yao, Yadong; Wu, Xingliang; Zhang, Jianxin; Zhu, Chen-guang; Xu, Feiyang; Xu, Sen (Process safety and environmental protection, 2023)
The knowledge of hazard classification of hydroxylammonium nitrate (HAN)-based liquid propellant is an essential subject in prevention of safe and transportation accidents. To improve hazard classification of the propellant, various tests were conducted on both material sample and packaged sample. Differential scanning calorimeter was utilized to study thermal decomposition parameters, resulting in the determination of high values for both thermal decomposition and explosion temperatures. Koenen and EIDS gap tests were used to evaluate the heat response under high confinement and the sensitivity of shock, respectively. The results indicated that the propellant was insensitive to shock wave, with a limiting diameter of 3.0 mm. The external fire test was conducted to elucidate the explosion characteristics of the packaged propellant. Pictorial information and temperature data were recorded using high-speed camera and infrared imager. The results revealed that a mass explosion occurred during the fire process. The combination of the perforated witness screen, long-range metallic projections and high-value heat flux led to the classification of the packaged HAN-based liquid propellant as Class 1.1 C, more stringent than the traditional Class 1.3 C. The study is expected to offer valuable insights for the safety of development, preservation, and conveyance of HAN-based liquid propellant.